(untitled) (Dhaka University Journal of Pharmaceutical Sciences, 2025)
This study investigated the phytochemical constituents and pharmacological potential of Parmentiera aculeata a medicinal plant used traditionally in Central America. Four compounds were isolated and characterized, namely oleic acid (1), methyl palmitate (2), 7,9-pentadecanediol (3), and methyl 5-eicosenoate (4). The ethylacetate-soluble fraction (PAEA) and aqueous fraction (PAA) exhibited potent antioxidant activity (IC50=12.65 µg/ml) which correlated with their high phenolic content (47.62 and 47.54 mg GAE/g, respectively). In the brine shrimp lethality assay, the PAD fraction demonstrated significant cytotoxicity (LC50=0.258 µg/ml) in the brine shrimp lethality assay. PAEA showed excellent thrombolytic activity (45.99%) comparable to the standard (65.09%). All fractions exhibited anti-inflammatory effects, with PAEA and PAA achieving 95.70% and 86.97% inhibition in heat-induced hemolysis, respectively. In hypotonic solution induced hemolysis, only PAA exhibited promising result (49.6%). The plant crude extract (PA) exhibited analgesic activity in the acetic acid-induced writhing assay (p<0.05 for 200 mg/kg, p<0.01 for 400 mg/kg) and antidiarrheal effects (58.97% for both doses, p<0.01). Moreover, PA exhibited a dose-dependent hypoglycemic effect, with a 58.99% reduction in plasma glucose at 400 mg/kg. These findings suggest that P. aculeata possesses promising pharmacological properties and warrants further investigation in order to create possible therapeutic medicines. Dhaka Univ. J. Pharm. Sci. 24(1): 77-86, 2025 (June)